Role of pre-emptive analgesia in post operative Pain management - a review of literature (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
DOI: http://dx.doi.org/10.3329/jbsa.v23i2.18176 Journal of BSA, 2009; 23(2): 62-66